SISTEM INFORMASI MANAJEMEN PENDIDIKAN DI SEKOLAH - Marwan, Edi (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2018)
People who live before the arrival of the information age,handling information is done manually or mechanically by using machines that are not computers. However, in entering a new era, the world community is now also in an era of knowledge-based society. In addition, the world is in an era of information and communication. Which at the moment we are in the information age, this means that information has touched all aspects of life, both individuals, groups and organizations. At the individual level various kinds of information are needed such as the need for education, health, employment, and other types of products or services.